2007
DOI: 10.1103/physrevlett.99.120505
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-Optics Implementation of an Asymmetric Phase-Covariant Quantum Cloner

Abstract: We present the experimental realization of optimal symmetric and asymmetric phase-covariant 1 → 2 cloning of qubit states using fiber optics. State of each qubit is encoded into a single photon which can propagate through two optical fibers. The operation of our device is based on one-and two-photon interference. We have demonstrated creation of two copies of any state of a qubit from the equator of the Bloch sphere. The measured fidelities of both copies are close to the theoretical values and they surpass th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 24 publications
(33 reference statements)
0
31
0
Order By: Relevance
“…The relation between optimal quantum cloning and the security of these QKD protocols was studied in various works (see, e.g., Refs. [38][39][40][41][42] and references therein). This connection to optimal quantum copying is anticipated since the security of the MUB-based QKD protocols is guaranteed by the impossibility of ideal copying of an unknown quantum state [43,44].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The relation between optimal quantum cloning and the security of these QKD protocols was studied in various works (see, e.g., Refs. [38][39][40][41][42] and references therein). This connection to optimal quantum copying is anticipated since the security of the MUB-based QKD protocols is guaranteed by the impossibility of ideal copying of an unknown quantum state [43,44].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The security of these QKD protocols is naturally related to optimal quantum cloning and it was studied in various works (see, e.g., Refs. [36,[40][41][42][43] and references therein). It was recently shown that the TS parameter S N depends on the average QBER r N or the average fidelity F N = 1 − r N of the states received by Bob [33].…”
mentioning
confidence: 99%
“…For balanced chip-scale splitting, we note that multi-mode interference [35] and Y-splitters are also good elements for physical realization. Directional couplers on the other hand provides differential and accurate thermal tuning on the SR, enabling controlled asymmetries such as for various C-NOT gate [53], quantum cloning [54,55], and Fock state filtration [56,57] applications. Supported by these designs, the devices were next fabricated at the Institute of Microelectronics.…”
Section: Design and Fabrication Of Silicon Chip-scale Two-photon Intementioning
confidence: 99%